Assessment of psychometric properties of patient education tools for oral anticoagulants - Santosha Vooradi, Gabriel Sunil Rodrigues, Tom Devasia, Ganesh Sevagur Kamath, Vilakkathala Rajesh (Journal of Applied Pharmaceutical Science, 2024)
Anticoagulation information leaflets help the patient to understand regarding their disease, medications, and lifestyle modifications which aid in adhering to their treatment. The primary objective of the research is the development and assessment of psychometric properties of patient education tools on oral anticoagulants and warfarin pharmacogenetics. In this study, a patient education tool was developed by using an evidence-based literature search. The physicians and academic pharmacists validated the content of the patient education tool. The validated patient education tool was assessed for its readability, layout, and design. The patient education tool was assessed for psychometric properties includes validity, reliability, and responsiveness. “Item-content validity index” (I-CVI) and “scale-level CVI” (S-CVI) were used to assess the anticoagulation knowledge questionnaire. The change in knowledge score was analyzed using the paired-“t” test. For the readability assessment, the best FRE and FK-GL scores achieved are 62.3 and 8.1, respectively, for the anticoagulant patient education tool. Both readability scores rate the patient education tool as “standard”. The developed anticoagulant knowledge questionnaire showed an overall I-CVI of 0.81. The knowledge scores before and after using the patient education tool were 55 + 21.21 and 80 + 14.14 (p < 0.001). The readability and design criteria of the patient education tools were standard and had good layout and design. The knowledge questionnaire demonstrates a valid and reliable instrument to be utilized for concurrent assessment in patients prescribed anticoagulants. In the study, the developed patient education tools had good psychometric properties.
Keywords: Patient education tools, psychometric properties, anticoagulants, content validity, knowledge